A ROLE AND IMPECT OF INTERNATIONAL ORGANIZATIONS IN INTERNATIONAL RELATIONS IN THE DIRECTION OF THE PROTECTION OF HUMAN RIGHTS AND THE RIGHTS TO THE ENVIRONMENT - Filipovski, Zoran; Nuredin, Abdulmecit; Sotiroska, Kalina; Galetin, Milena (International Scientific Journal Vision, 2018)
International organizations are essential actors that influence international relations in the international system, because their infl uence in many cases has a positive eff ect on resolving the problems that are more common in international political relations, driven by the interests of states, and аre related to issues of environmental disasters, nuclear danger, climate change, economic development and the protection of human rights. The text will cover the genesis of international organizations and their infl uence on the development and changes ininternational relations, which will positively refl ect on the eff orts of the countries in terms of environmental protection. In the context of this, the infl uence of these organizations on the states in terms of the acceptance of the provisions of international agreements as sources of horizontal legislation in the fi eld of environment is of signifi cant importance. In the context of this, of substantial importance is the impact of these organizations on the states in terms of acceptance of the provisions of international agreements as sources of horizontal legislation in the fi eld of environment.